Thermometry in a multipole ion trap - Nötzold, Markus; Hassan, Saba; Tauch, Jonas; Endres, Eric; Wester, Roland; Weidemüller, Matthias (Applied Sciences, 2020)
We present a characterization of the ions’ translational energy distribution in a multipole ion trap. A linear mapping between the energy distribution of the trapped ions onto the ions’ time-of-flight (TOF) to a detector is demonstrated. For low ion temperatures, a deviation from linearity is observed and can be attributed to the emergence of multiple potential minima. The potential landscape of the trapped ions is modeled via the finite element method, also accounting for subtleties such as surface-charge accumulation. We demonstrate the validity of our thermometry method by simulating the energy distribution of the ion ensemble thermalized with buffer gas using a Molecular Dynamics (MD) simulation. A comparison between the energy distribution of trapped ions in different multipole trap configurations—i.e., with hyperbolic rods, cylindrical rods, and cylindrical wires—is provided. With these findings, one can map the temperature of the trapped ions down to the Kelvin regime using their TOF distributions. This enables future studies on sympathetic cooling and chemical reactions involving ions in multipole traps.